Valor predictivo positivo del ultrasonido en la clasificación TI-RADS. - Montaño-Ascencio, P. G.; García-Baeza, L. G.; Gómez-Vargas, E.; Pérez-Hernández, J. U. (Anales de Radiologia, Mexico)
Background: thyroid nodules have a prevalence of 67% in the adult human population. There is a pressing need to unify ultrasonographic criteria and parameters to identify cancer and to define benignancy with adequate predictive value. For this purpose, the TI-RADS (Thyroid Imaging Reporting and Data System) system of classification of thyroid nodules has been proposed. Objective: determine positive and negative predictive values, sensitivity and specificity of TI-RADS classification to standardize it and use it at Hospital General Regional de Leon. Material and methods: study with a series of cases of patients referred to the Oncological Radiology service with clinical diagnosis of thyroid nodule; all patients who met all the established criteria were selected. Thyroid nodules were characterized with variables for the TI-RADS classification method. Results: of 37 nodules characterized (benign: 28; follicular neoplasm: 1, and carcinoma: 8), the sensitivity, specificity, positive predictive value, and negative predictive value were: 87, 88, 80, and 93%, respectively, for TI-RADS 5. Conclusion: TI-RADS classification is useful to standardize and characterize reporting of thyroid lesions to unify criteria, language and management of thyroid images diagnosed by echogram between the clinician and the radiologist.